Earthquakes and eschatology in the gospel according to Matthew - Carrier, Brian 1981-; Catholic University of America; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2020)
In dieser Studie untersucht Brian Carrier die Rolle seismischer Begrifflichkeit im Matthäusevangelium. Mittels eines narrativ-kritischen Ansatzes argumentiert er, dass die seismischen Hinweise bei Matthäus Jesu Leben, Tod und Auferstehung als Teilerfüllung alttestamentlicher Prophezeiungen über den Tag des Herrn darstellen.
In this study, Brian Carrier provides a comprehensive analysis of the role that seismic language plays within the Matthean Gospel narrative. After reconstructing what connotations seismic language likely carried in Matthew's cultural context, the author utilizes an historically informed author-oriented narrative criticism that is complemented with redaction criticism to analyze the relationships that Matthew's seismic references display with regards to each other and to the overall narrative. This analysis leads to the conclusion that Matthew's seismic references collectively indicate that the life, death, and resurrection of Jesus together represent the partial fulfillment of the Old Testament eschatological Day of the Lord.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe; Völkerwanderung; Teilhabe; Interreligious encounters; Allgemeines/Besonderes; Editing; Narrative Criticism; Narrative Criticism; Day of the Lord; Seismic; Shaking; Characterization; Altes Testament; Neues Testament; Array; Neoplatonism; Hochschulschrift